2010
DOI: 10.1029/2008wr007445
|View full text |Cite
|
Sign up to set email alerts
|

Environmental water incentive policy and return flows

Abstract: [1] With increasing urban, industrial, and agricultural water demand and projected reduced supply under climate change, allocations to the environment are critically low in many arid and semiarid basins. Consequently, many governments are striving to augment environmental flows, often through market-oriented mechanisms that involve compensating irrigated agriculture, the largest water user in most basins, for reducing diversions. A widely documented challenge with policies to recover water for the environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(57 citation statements)
references
References 19 publications
2
53
0
2
Order By: Relevance
“…Other authors give ambiguous results such as Dinar and Zilberman (1991), Qureshi et al (2010), Huffaker (2008) and Gómez and Pérez (2013) where the final result of water saving investment is ambiguous with the rebound effect that would be a function of water cost and water productivity and the implementation measures selected for financing the water savings policy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors give ambiguous results such as Dinar and Zilberman (1991), Qureshi et al (2010), Huffaker (2008) and Gómez and Pérez (2013) where the final result of water saving investment is ambiguous with the rebound effect that would be a function of water cost and water productivity and the implementation measures selected for financing the water savings policy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a mathematical programming model of the Murray Darling basin, Qureshi et al (2010) concluded that efficiency-improving investments could provide some costeffective opportunities, but also that the final net result is ambiguous and depends on the previous return flows and the use of the water savings. The critical element in most of the published research is the existence of a good water accounting framework.…”
Section: Mathematical Programmingmentioning
confidence: 99%
“…Los mercados de agua reducen los caudales de los ríos porque se venden derechos de agua que anteriormente no se utilizaban, pero también porque se generan ganancias de eficiencia de riego en parcela que reducen los retornos de riego de cuenca (Quereshi, M. et al, 2010). La razón es que se transfiere agua de zonas de baja eficiencia poco rentables a zonas de alta eficiencia más rentables, por lo que caen los retornos de riego.…”
Section: -Impactos Medioambientales De La Transferencia De Derechosunclassified
“…For consumptive water uses, such as irrigation, the maximum tradable water is the average volume of water actually consumed. This effective consumption is calculated as the difference between the volume of water extracted from the source and the return flows, taking into account the efficiency in the transportation, distribution and crop watering [18][19][20]. Regardless of the average volume of water actually used, the volume of water transferred cannot exceed the amount of water allocated by the corresponding River Basin Authorities (RBA) on the basis of the hydrological year.…”
Section: Institutional Framework Of Water Markets In Spainmentioning
confidence: 99%